2012
DOI: 10.1021/jf302831d
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Upregulates Nrf2 Expression To Attenuate Methylglyoxal-Induced Insulin Resistance in Hep G2 Cells

Abstract: Oxidative stress can result in insulin resistance, a primary cause of type-2 diabetes. Methylglyoxal (MG), a highly reactive dicarbonyl metabolite generated during glucose metabolism, has also been confirmed to cause pancreatic injury and induce inflammation, thereby resulting in insulin resistance. Recently, resveratrol has been reported to exert antioxidant properties, protecting cells from the generation of reactive oxygen species (ROS). The aim of this study was to evaluate resveratrol activation of nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 64 publications
8
91
0
1
Order By: Relevance
“…In addition, resveratrol has properties to decrease ROS ) and stimulate PPARa involved in fatty acid oxidation (Nakata et al 2012). Moreover, previous studies reported that resveratrol improved insulin resistance by promoting HO-1 protein through mediating Nrf2 level in HepG2 cell (Cheng et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, resveratrol has properties to decrease ROS ) and stimulate PPARa involved in fatty acid oxidation (Nakata et al 2012). Moreover, previous studies reported that resveratrol improved insulin resistance by promoting HO-1 protein through mediating Nrf2 level in HepG2 cell (Cheng et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Nrf2 activation in human liver cells improved glucose uptake [77]. Micro-vascular diabetic complications such as nephropathy [78][79] and neurological dysfunction [80][81] have been evaluated in vitro.…”
Section: Nrf2 Activation By Natural Compoundsmentioning
confidence: 99%
“…We have previously observed a marked impairment of the Nrf2 system in mice fed a high-fat diet (HFD) [9,10] and that correcting defective Nrf2 function via supplementation with the chemical Nrf2 activator oltipraz not only attenuated oxidative stress but also improved insulin signaling and glucose metabolism [10] . Other synthetic chemical Nrf2 activators and natural Nrf2-activating compounds have also been shown to be effective in improving insulin action and glucose metabolism in various insulin-resistant models [9,[11][12][13] . In addition, there is probably an interaction between oxidative stress and inflammatory activation.…”
Section: Introductionmentioning
confidence: 99%